Analisis Membaca Pemahaman Dengan Penerapan Metode Mind Mapping Pada Siswa Kelas IV SDN 19 Setogor - Warnik Warnik; Lilianslow Lilianslow (LPPM Institut Pendidikan Nusantara Global, 2026)
Reading comprehension is a fundamental literacy competence in elementary education because it determines students' ability to identify main ideas, locate explicit information, draw conclusions, and connect ideas in a text. However, classroom reading activities often focus on answering questions without sufficiently guiding students to organize textual information. This study addresses that gap by describing students' reading comprehension after the application of the mind mapping method and identifying the aspects of comprehension that still require instructional support. The study used a descriptive qualitative approach involving 29 fourth-grade students at SDN 19 Setogor. Data were collected through a reading comprehension test and documentation. The test instrument was developed based on indicators of reading comprehension, including identifying main ideas, finding detailed information, summarizing text content, and retelling the text in students' own words. Data were analyzed through score tabulation, percentage calculation, categorization, and qualitative interpretation of students' difficulties. The findings show that one student (3.45%) was in the very good category, sixteen students (55.17%) were in the good category, one student (3.45%) was in the sufficient category, and eleven students (37.93%) were in the poor category, with a class mean score of 63.10. These results indicate that mind mapping can support students in organizing reading information, but it needs to be accompanied by vocabulary enrichment, explicit guidance in identifying main ideas, and repeated practice in drawing conclusions. The contribution of this study lies in providing classroom-based evidence that mind mapping is useful as a visual strategy for reading comprehension while also highlighting the need for more structured literacy scaffolding in elementary Indonesian language learning.